MALDI-TOF MS Profiling-Advances in Species Identification of Pests, Parasites, and Vectors - Murugaiyan, Jayaseelan; Roesler, Uwe (Frontiers in Cellular and Infection Microbiology, 2017)
Invertebrate pests and parasites of humans, animals and plants continue to cause serious diseases and remain as a high treat to agricultural productivity and storage. The rapid and accurate species identification of the pests and parasites are needed for understanding epidemiology, monitoring outbreaks and designing control measures. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) profiling has emerged as a rapid, cost effective and high throughput technique of microbial species identification in modern diagnostic laboratories. The development of soft ionization techniques and the release of commercial pattern matching software platforms has resulted in the exponential growth of applications in higher organisms including parasitology. The present review discusses the proof-of-principle experiments and various methods of MALDI MS profiling in rapid species identification of both laboratory and field isolates of pests parasites and vectors.